Carbon-11 N-methyl alkylation of L-368,899 and in vivo PET imaging investigations for neural oxytocin receptors - Smith, Aaron L. (2012)
Compound L-368,899 was successfully alkylated with [(11)C]iodomethane to generate the oxytocin receptor selective (2R)-2-amino-N-((2S)-7,7-dimethyl-1-(((4-(o-tolyl)piperazin-1-yl)sulfonyl)methyl)bicyclo[2.2.1]heptan-2-yl)-N-[(11)C]methyl-3-(methylsulfonyl)propanamide ([(11)C]1) with very high radiochemical purity and high specific activity. PET imaging studies were performed with [(11)C]1 to investigate brain penetration and oxytocin receptor uptake using rat and cynomolgus monkey models. For rat baseline scans, brain penetration was observed with [(11)C]1, but no specific uptake could be distinguished in the brain region. By administering a peptide oxytocin receptor selective antagonist for peripheral blocking of oxytocin receptors, the uptake of [(11)C]1 was amplified in the rat brain temporarily to enable some visual uptake within the rat brain. A baseline scan of [(11)C]1 in a cynomolgus monkey model resulted in no detectable specific uptake in anticipated regions, but activity did accumulate in the choroid plexus.